A preliminary investigation of insect succession patterns on decomposing carrion on Rottnest Island (WA) / Abrar Essarras ... [et al.] - Essarras, Abrar; Dadour, Ian R.; O'Brien, R. Christopher; Magni, Paola A. (Faculty of Medicine, Universiti Teknologi MARA, 2021)
Introduction: Pivotal component of medico-legal investigations is the determination of time since death, or (minimum) postmortem interval, (min)PMI. Forensic entomology can provide reliable estimates of (min)PMI using carrion insect species. Carrion insect arrival and departure occurs in predictable and sequential waves, however, successions may vary depending on geographical location and environmental conditions. Hence, it is crucial to refer to insect succession data of the same region where the death scene occurs. A current gap in forensic entomology research is on carrion-breeding species and succession on decomposition remains/carrions on small islands. Rottnest Island is located off the south-west coast of Perth. The aim of this study was to establish baseline data of carrion insect fauna present on this island, and to provide entomological evidence that may aid in any future investigations on the island. Methods: A list of the insect taxa associated with two decomposing swine hindquarters during the summer season was compiled over a 15-day study period and compared with published mainland data obtained during the same period of the year. Results: Ten insect taxa representing four families were collected and identified in association with the decomposing carrion. The first wave of colonising Diptera species included Calliphoridae species and Sarcophagidae species. The second wave of Diptera comprised Muscidae species, in addition to beetles. Furthermore, ants and spiders were noted throughout the trial. Conclusions: Comparing the results on Rottnest Island with currently available data from mainland WA, showed that the composition of insect species and the patterns of succession were similar.